PRODUCT ASSORTMENT AND CUSTOMER PATRONAGE OF FILLING STATIONS IN YENAGOA, BAYELSA STATE - Ademe-Godwin, Doris; Opuene, James Endurance (American Journals Publishing, 2023)
The aim of this research work was to empirically investigate the relationship between product assortment and customer patronage of filling stations in Yenagoa, Bayelsa State. This study employed the cross-sectional survey research design. The researcher made use of 300 customers from 20 accessible filling stations that patronize filling stations in Yenagoa, Bayelsa State that were accessible to the researcher. Spearman Rank Correlation Coefficient was used to test the four hypotheses. This result indicated that there is a significant relationship between product assortment and customer patronage of filling stations in Yenagoa, Bayelsa State. The researcher therefore recommended that managers of filling stations in Yenagoa, Bayelsa State are encouraged to treat product width as an essential marketing strategy that should, as a matter of policy, be better managed for sustainable customer patronage and profitability.